2015
DOI: 10.1038/pr.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between T-cell HLA-DR expression and intravenous immunoglobulin treatment response in Kawasaki disease

Abstract: Background: Kawasaki disease (KD) is an acute febrile illness associated with the development of vasculitis. Administration of intravenous immunoglobulin (IVIG) is the standard treatment for KD. However, IVIG treatment is not effective in approximately 15% of children with KD. Some reports have presented evidence of immunological responses in IVIG-resistant KD patients.We assessed the possibility that T-cell activation is a contributing mechanism underlying this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…It is well known that KD is associated with increased immune system activation, increased complement activation, and increased antibody‐dependent cell‐mediated cytotoxicity, all of which could theoretically lead to increased hemolysis. Patients with refractory KD in particular have increased interleukin (IL)‐1 levels, increased CRP, and increased neutrophil percentage, markers of T‐cell activation such as increased T‐cell HLA‐DR expression, lack of reduction of soluble IL‐2 receptor, and IL‐6 in response to IVIG . The relationship between inflammation and hemolysis in our cohort was not straightforward, as there was not a clear difference between the levels of inflammatory markers ESR and CRP at presentation in patients who did and did not develop hemolysis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is well known that KD is associated with increased immune system activation, increased complement activation, and increased antibody‐dependent cell‐mediated cytotoxicity, all of which could theoretically lead to increased hemolysis. Patients with refractory KD in particular have increased interleukin (IL)‐1 levels, increased CRP, and increased neutrophil percentage, markers of T‐cell activation such as increased T‐cell HLA‐DR expression, lack of reduction of soluble IL‐2 receptor, and IL‐6 in response to IVIG . The relationship between inflammation and hemolysis in our cohort was not straightforward, as there was not a clear difference between the levels of inflammatory markers ESR and CRP at presentation in patients who did and did not develop hemolysis.…”
Section: Discussionmentioning
confidence: 80%
“…Patients with refractory KD in particular have increased interleukin (IL)-1 levels, increased CRP, and increased neutrophil percentage, 21 markers of Tcell activation such as increased T-cell HLA-DR expression, lack of reduction of soluble IL-2 receptor, and IL-6 in response to IVIG. [23][24][25] The relationship between inflammation and hemolysis in our cohort was not straightforward, as there was not a clear difference between the levels of inflammatory markers ESR and CRP at presentation in patients who did and did not develop hemolysis. Macrophage activation syndrome (MAS) is an important complication of KD that may manifest with an acute decrease in Hb and may be underrecognized.…”
Section: Discussionmentioning
confidence: 86%
“…However, there has been no report in which any aggressive therapy prevented coronary artery lesions in patients at high risk of unresponsiveness predicted by biomarkers and genetic variants. For more information about studies of biomarkers and genetic variants, two recent reviews are informative [74,75] . More-aggressive initial treatment for patients at a high risk of IVIG unresponsiveness after risk stratification using a predictive model has been recommended in the recently updated guidelines for the medical treatment of acute Kawasaki disease in Japan [39] .…”
Section: Combination With Ivig As the Routine First Line Treatmentmentioning
confidence: 99%
“…Circulating monocyte/macrophages, rather than T cells, are reported to be activated during the acute phase of KD . We have reported that increased HLA‐DR expression on CD4 + T cells or CD8 + T cells is associated with IVIG resistance in KD patients . Repeated IVIG could sufficiently control the activation of monocytes/macrophages or coronary arterial endothelial cells but not the activation of T cells .…”
Section: Discussionmentioning
confidence: 96%
“…1 We have reported that increased HLA-DR expression on CD4 + T cells or CD8 + T cells is associated with IVIG resistance in KD patients. 15 Repeated IVIG could sufficiently control the activation of monocytes/macrophages or coronary arterial endothelial cells but not the activation of T cells. 1 With regard to this, a shift to T cell activation might account for the pathophysiology of refractory KD in young infants.…”
Section: Discussionmentioning
confidence: 99%